A Rare Case of Caecal Desmoid Tumor - Anas Elwassi; Khalid Jamaleddine; Ayoub Amor; Kenza Benjelloune; Amal Hajri; Driss Erguibi; Rachid Boufettal; Saad Jai Rifki; Farid Chehab (European Scientific Journal, ESJ, 2025)
Desmoid tumors (DTs) are rare, benign fibroblastic neoplasms with local aggressiveness but no metastatic potential. We report a 16-year-old woman with chronic right lower quadrant pain and an abdominopelvic mass, initially suspected to be a gastrointestinal stromal tumor. Surgical excision confirmed a caecal desmoid tumor. DTs can mimic malignancies, requiring MRI, histopathology, and immunohistochemistry for diagnosis. Treatment varies, with surgery for symptomatic cases and emerging systemic therapies as alternatives. This article aims to raise awareness of these rare tumors in unexpected locations. It highlights the importance of considering DTs in the differential diagnosis of abdominal masses, particularly in young patients, and emphasizes the need for genetic counseling and multidisciplinary management.